Various approaches to measuring business innovation: Their relevance for capturing social innovation - Attila Havas (Hungarian Academy of Sciences, Institute of Economics, 2015)
This paper reviews various approaches to measuring business innovation from the angle of capturing social innovations and offers several methodological and policy conclusions. First, the Innovation Union Scoreboard (IUS) indicators in principle could be useful in settings where the dominant mode of innovation is based on R&D activities. In practice, however, both R&D and non-R&D-based modes of innovation are fairly important. IUS, therefore, only provides a partial picture. Social innovations can certainly rely on R&D-based technological innovations. Their essence, however, tends to be organisational, managerial and behavioural changes. The IUS indicators do not capture these types of changes. Second, an assessment of the 81 indicators used to compile the Global Innovation Index reveals that it would neither be a fruitful effort to rely on those indicators to capture social innovations. Third, given the diversity among innovation systems, a poor performance signalled by a composite indicator does not automatically identify the area(s) necessitating the most urgent policy actions. Only tailored, thorough comparative analyses can do so. Fourth, analysts and policy-makers need to be aware of the differences between measuring (i) social innovation activities (efforts) themselves, (ii) the framework conditions (pre-requisites, available inputs, skills, norms, values, behavioural patterns, etc.) of being socially innovative, and (iii) the economic, societal or environmental impacts of social innovations.
Keywords: B52; C80; O31; O35; O38; Y10; 330; Evolutionary economics of innovation; Business innovation; Social innovation; Measurement of innovation; Composite indicators; Scoreboards; league tables; Unit of analysis